Theoretical Writing - Barney G. Glaser (Grounded Theory Review: An International Journal, 2009)
The goal of grounded theory methodology, above all is to offer the results to the public, usually through one or more publications. We will focus on writing for publication, which is the most frequent way that the analyst can tell how people are “buying” what really matters in sociology, or in other fields.